Analysing e-government service quality in Greece. (5th October 2011) - Papadomichelaki, Xenia; Mentzas, Gregoris
Motivated by the growing interest in e-government, our research aims to discover the quality priorities of e-government users and analyses the attitude of Greek citizens towards e-government sites in Greece. We propose a research model which posits four dimensions influential to e-government site quality – efficiency, trust, reliability, citizen support. Data was collected and analysed to gather information concerning the way Greek users interact with e-government. We found that all four dimensions significantly influence citizens' evaluation and intention to reuse. E-government users perceived different importance of quality factors in using different types of e-government sites.